Antam Marketing Mix Strategy Group - Frans Sudirjo; I Nyoman Tri Sutaguna; Kaharuddin Kaharuddin; Arief Yanto Rukmana; Betty Rahayu (Wawasan : Jurnal Ilmu Manajemen, Ekonomi dan Kewirausahaan, 2023)
As a result, the goal of this article is to examine the marketing mix used by Antam's Padjadjaran Branch Group to market gold savings products, to evaluate the limitations and challenges faced by the marketing mix within the Antam Group Pajajaran Branch, and to develop marketing strategy recommendations to address both internal and external challenges encountered during the process of marketing gold savings products at the Antam Group Pajajaran Branch. Data for this study was acquired through interviews, observations, and recording using a qualitative descriptive methodology. The Antam Pajajaran Group Branch Managers, the Antam Pajajaran Branch Group Marketing Department, and the Gold Savings Products Pajajaran Bandung Branch's clients served as the study's informants. This study used the marketing mix theory as a guide. The study's conclusions include the marketing tactics used by Antam Group's Pajajaran Branch, which apply segmentation, targeting, and positioning principles, as well as the marketing mix, which includes product, price, place, promotion, people, processes, and facilities.